Specific Cleavage of Simian Virus 40 DNA by Restriction Endonuclease of Hemophilus Influenzae - Danna, Kathleen (1971)
A bacterial restriction endonuclease has been used to produce specific fragments of SV40 DNA. Digestion of DNA from plaque-purified stocks of SV40 with the restriction endonuclease from Hemophilus influenzae gave 11 fragments resolvable by polyacrylamide gel electrophoresis, eight of which were equimolar with the original DNA. The fragments ranged from about 6.5 × 10(5) to 7.4 × 10(4) daltons, as determined by electron microscopy, DNA content, or electrophoretic mobility.